Reproducibility of Apparent Diffusion Coefficient Measurements in Malignant Breast Masses - Jang, Mijung (J Korean Med Sci, 2015)
This study aimed to evaluate the reproducibility of apparent diffusion coefficient (ADC) measurements in malignant breast masses, and to determine the influence of mammographic parenchymal density on this reproducibility. Sixty-six patients with magnetic resonance findings of the mass were included. Two breast radiologists measured the ADC of the malignant breast mass and the same area on the contralateral normal breast in each patient twice. The effects of mammographic parenchymal density, histology, and lesion size on reproducibility were also assessed. There was no significant difference in the mean ADC between repeated measurements in malignant breast masses and normal breast tissue. The overall reproducibility of ADC measurements was good in both. The 95% limits of agreement for repeated ADCs were approximately 30.2%-33.4% of the mean. ADC measurements in malignant breast masses were highly reproducible irrespective of mass size, histologic subtype, or coexistence of microcalcifications; however, the measurements tended to be less reproducible in malignant breast masses with extremely dense parenchymal backgrounds. ADC measurements in malignant breast masses are highly reproducible; however, mammographic parenchymal density can potentially influence this reproducibility.